ДИДАКТИЧНІ УМОВИ ФОРМУВАННЯ ПРИРОДОЗНАВЧОЇ КОМПЕТЕНТНОСТІ УЧНІВ ПОЧАТКОВИХ КЛАСІВ В УМОВАХ ІНКЛЮЗИВНОГО НАВЧАННЯ - Голуб Н. П.; Голуб В. М. (World Science, 2019)
The article deals with the formation peculiarities of natural science competence of elementary school students. The definitions of "competency" and "competence" are specified. The literary analysis indicated a lack of study of the investigated problem in the context of educational reform. Didactic conditions for the formation of natural science competence in conditions of inclusive education are determined. The emphasis is focused on pedagogical technologies that involve individualization, differentiation and integration of learning. Integrated lessons contribute to the formation of substantive and interdisciplinary key competencies. In 1-2 classes the formation of natural science competence should be based on an integrated-subject basis with the predominance of game techniques. In 3-4 classes the formation of natural science competence should be based on an integrated-subject basis with the predominance of means of individualization and differentiation.